2007
DOI: 10.1248/bpb.30.994
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Trimidox on Oxidative Stress in U937 Cell Line

Abstract: Trimidox (3,4,5-trihydroxybenzamidoxime) is one of the most potent ribonucleotide reductase inhibitors, revealing an antitumor effect in several experimental studies. We have examined the effect of trimidox on the induction of cytotoxicity and apoptosis via oxidative stress by typical free radical inducers, hydrogen peroxide (H 2 O 2 ), tert-butylhydroperoxide (tBuOOH) or ultraviolet (UV) irradiation in a human diffuse histiocytic lymphoma U937 cell line. Trimidox showed strong radical scavenging activity by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On contrary, DID can be described to possess sensitizing role for DOX-induced cytotoxicity in CRC cells. This might be similar to the effect of trimidox, another ribonuclueotide reductase inhibitor, which exhibits both anticancer and potent antioxidant properties57. DID is known to be a ribonucleotide reductase enzyme inhibitor which might partly explain its anti-proliferative and chemosensitizing effects33.…”
Section: Discussionmentioning
confidence: 87%
“…On contrary, DID can be described to possess sensitizing role for DOX-induced cytotoxicity in CRC cells. This might be similar to the effect of trimidox, another ribonuclueotide reductase inhibitor, which exhibits both anticancer and potent antioxidant properties57. DID is known to be a ribonucleotide reductase enzyme inhibitor which might partly explain its anti-proliferative and chemosensitizing effects33.…”
Section: Discussionmentioning
confidence: 87%
“…Several RR inhibitors including HU [27], DFO [27], resveratrol [26], and trimidox [28] are all known to scavenge diverse radical species. To test whether KP772 can protect cells from reactive oxygen species (ROS), KB-3-1 cells were treated in presence of subtoxic concentrations of KP772 (0.5 and 1 μM) with various concentrations of H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It is variously reported that ribonucleotide reductase inhibitors may have anticarcinogenic effects and induce apoptosis (15) or may be endowed with the possibility to inhibit the induction of apoptosis via oxidative stress (54). This enzyme seems to be only marginally involved in the apoptosis of CGCs since its inhibition by hydroxyurea (55) has only a small effect both in improving cell survival and reducing superoxide anion levels.…”
Section: Discussionmentioning
confidence: 99%